Management of obstetric anal sphincter injuries (OASIS) in subsequent pregnancy. (August 2014) - Evans, C.; Archer, R.; Forrest, A.; Barrington, J.
Abstract Obstetric anal sphincter injuries (OASIS) are common and may greatly affect a patient's quality of life. There is very little information regarding optimum management in future pregnancies. Based upon anecdotal experience, this study describes the recommendations of a cohort of consultant obstetricians in the UK, in this clinical situation. There is limited adherence to the available national guidelines due to the absence of available equipment and expertise to perform endo-anal ultrasound and manometry. Elective episiotomy is still recommended by a small number of obstetricians but the majority of patients are routinely followed-up. Caesarean section is only advised for asymptomatic patients with a previous stage 4 tear, and for any symptomatic patient with a previous stage 3 or 4 tear, irrespective of subgrade. A request for elective caesarean section is likely to be granted, irrespective of OASIS grade. The use of postpartum endo-anal ultrasound would help identify those women in whom a further vaginal delivery is unlikely to exacerbate any symptoms of faecal incontinence.